2011
DOI: 10.1111/j.1525-1594.2010.01124.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation in Ovines Undergoing Sham Surgery or Implant of the Second Generation PediaFlow Pediatric Ventricular Assist Device

Abstract: The PediaFlow™ pediatric ventricular assist device (VAD) is a magnetically levitated turbodynamic pump under development for circulatory support of small children with a targeted flow rate range of 0.3 - 1.5 L/min. As the design of this device is refined, ensuring high levels of blood biocompatibility is essential. In this study we characterized platelet activation during the implantation and operation of a second generation prototype of the PediaFlow VAD (PF2) and also performed a series of surgical sham stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 31 publications
3
41
0
Order By: Relevance
“…Given the known thromboembolic, bleeding, and infectious complications associated with the use of ECMO [19, 20], it raises the question of whether the observed early mortality in the ECMO BTT group would be markedly reduced if durable VAD support were made available to the smallest children requiring MCS as a BTT. A number of devices currently under development [21], including the infant Jarvik 2000 [22] and PediaFlow [23], could help to answer this question if brought to clinical trial.…”
Section: Commentmentioning
confidence: 99%
“…Given the known thromboembolic, bleeding, and infectious complications associated with the use of ECMO [19, 20], it raises the question of whether the observed early mortality in the ECMO BTT group would be markedly reduced if durable VAD support were made available to the smallest children requiring MCS as a BTT. A number of devices currently under development [21], including the infant Jarvik 2000 [22] and PediaFlow [23], could help to answer this question if brought to clinical trial.…”
Section: Commentmentioning
confidence: 99%
“…Recently, in the ovine model pediatric VAD biocompatibility has been characterized with flow cytometric assays that could detect platelet activation. [6, 1517] In several of these studies the assays demonstrated sensitivity in responding to animal and pump complications. [1617] Ovine sham studies were also previously performed to mimic the surgical insult for a VAD implant and demonstrated that the effects of surgery on platelet activation dissipate within approximately two weeks.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, decreased exposure will poten- tially mitigate the activation or destruction of cells, and thereby could potentially reduce hemolysis and thrombosis-a known serious adverse event associated with rotodynamic blood pumps. (7).…”
Section: Discussionmentioning
confidence: 95%